1986
DOI: 10.1016/s0006-3495(86)83712-2
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction analysis of cytochrome b5 reconstituted in egg phosphatidylcholine vesicles

Abstract: Cytochrome b5 was reconstituted asymmetrically into large unilamellar egg phosphatidylcholine vesicles. Asymmetry was preserved after sedimentation and partial dehydration to form oriented stacks of membranes. The periodicity of the centrosymmetric unit cell ranged between 145 and 175 A, depending upon the water content of the oriented multilayer. X-ray diffraction data were collected to a resolution of 12 A and phase factors were unambiguously assigned by a swelling analysis to a resolution of 15 A. The lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…The anchoring C-terminal peptide of cytochrome bs, reconstituted in its "tightly bound" form into lipid vesicles, may form a bent helix inserted part of the way into the bilayer. The evidence, however, is somewhat controversial (see Gogol, Engelman & ZaccaL 1983;Takagaki et al, 1983;Gogol & Engelman, 1984;Rzepecki, Strittmatter & Herbette, 1986;Arin% Rzepecki & Strittmatter, 1987) and not certain to reflect the native topology. To our knowledge, the two models initially proposed for PLP are unique in suggesting that a polytopic (multispanning) membrane protein features polypeptide segments looping back in the middle of the bilayer (Stoffel et al, 1983(Stoffel et al, , 1984Laursen et al, 1984;Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The anchoring C-terminal peptide of cytochrome bs, reconstituted in its "tightly bound" form into lipid vesicles, may form a bent helix inserted part of the way into the bilayer. The evidence, however, is somewhat controversial (see Gogol, Engelman & ZaccaL 1983;Takagaki et al, 1983;Gogol & Engelman, 1984;Rzepecki, Strittmatter & Herbette, 1986;Arin% Rzepecki & Strittmatter, 1987) and not certain to reflect the native topology. To our knowledge, the two models initially proposed for PLP are unique in suggesting that a polytopic (multispanning) membrane protein features polypeptide segments looping back in the middle of the bilayer (Stoffel et al, 1983(Stoffel et al, , 1984Laursen et al, 1984;Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Insight into the phase assignment for this particular reflection (quite important to the extent of bilayer asymmetry) was obtained by Patterson deconvolution ( Fig. 4; Skita et al, (Rzepecki et al, 1986). *Data from Rzepecki et al (1986) was d/2 shifted to obtain structure shown in manuscript.…”
Section: Fluorescence Anisotropymentioning
confidence: 99%
“…the phase set determined by Rzepecki et al (1986) and those derived by our evaluation of the structure factor plot (Fig. 3).…”
Section: CXmentioning
confidence: 99%
See 2 more Smart Citations